Parallel expression of macrophage metalloelastase (MMP-12) in duodenal and skin lesions of patients with dermatitis herpetiformis. Issue 4 (1st April 2001) - Salmela, M T; Pender, S L F; Reunala, T; MacDonald, T; Saarialho-Kere, U
Abstract : BACKGROUND: Dermatitis herpetiformis (DH) is a specific dermatological manifestation of coeliac disease and 80% of DH patients have gluten sensitive enteropathy manifested by crypt hyperplasia and villous atrophy. Matrix degradation mediated by collagenase 1 (MMP-1) and stromelysin 1 (MMP-3) has previously been implicated in the pathobiology of coeliac intestine and cutaneous DH blisters. AIMS: To study expression of stromelysin 2, metalloelastase, collagenase 3, and matrilysin in the intestine and skin of DH patients. METHODS: In situ hybridisation using 35 S labelled cRNA probes was performed on duodenal biopsies of 15 DH patients, three samples each of control duodenal or jejunal mucosa, fetal ileal explants, lesional DH skin, and 19 serial biopsies of experimental DH blisters. Immunostaining was used to examine type IV collagen, macrophages (CD68), and 92 kDa gelatinase (MMP-9) in the specimens. RESULTS: Metalloelastase (MMP-12) was abundantly expressed by subepithelial macrophages in both coeliac intestine and spontaneous and induced DH rash. It was also upregulated in the experimental model of coeliac disease (staphylococcal endotoxin B stimulated fetal explants). The only other MMP detected was MMP-9 which did not colocalise with MMP-12. CONCLUSIONS: Upregulation of metalloelastase is associated with T cell mediated immune responses both in the intestine and skin. In addition to modulating macrophage migration, it may contribute to degradation of proteoglycans or basement membrane components in the subepithelial mucosa.